Testing in Go : making the most of Go's testing package and tools (O'Reilly, 2017)
"Having access to a reliable and comprehensive test suite for your applications isn't a luxury anymore--it's a requirement. This video is the first in a series of 'Testing in Go' videos that teach you how to test your Go applications and make certain that what you ship works the first time. Designed for basic or intermediate level Go developers who want to start writing tests, write better tests, or increase the coverage of their current test suites, this course provides complete step-by-step instruction on how to write testable code."--Resource description page